Comparison between curettage adenoidectomy and endoscopic-assisted microdebrider adenoidectomy in terms of Eustachian tube dysfunction - Atilla,Mahmut Huntürk (2020)
Abstract Introduction Adenoidectomy can be performed with many ways, including curettage and microdebrider endoscopic-assisted adenoidectomy. Those two techniques have advantages and disadvantages. Objective The objective of this study is to research the effects of curettage adenoidectomy and endoscopic-assisted microdebrider adenoidectomy on the tympanum pressures in pediatric patients with adenoid hypertrophy without otitis media with effusion. Methods This prospective descriptive study was performed with 65 patients who had a normal tympanic membrane and normal tympanogram and then underwent adenoidectomy or adenotonsillectomy for adenoid and tonsil hypertrophy. The subjects were randomly divided into two groups: curettage adenoidectomy group and endoscopic microdebrider-assisted adenoidectomy group. They underwent tympanometry, and the preoperative as well as 1st and 7th day postoperative values of the tympanum pressures were compared within and among the groups. Results There were 32 patients in the curettage adenoidectomy group and 33 patients in the microdebrider adenoidectomy group. Statistically significant differences were observed in the median tympanum pressure on the preoperative and 1st and 7th postoperative days for both the left and right ears with curettage adenoidectomy (p < 0.001, p < 0.001). This difference occurred on the 1st postoperative day, and the value returned to normal on the 7th day. There was no significant difference in the median tympanum pressure on the preoperative and 1st and 7th postoperative days for both the left and right ears in the microdebrider adenoidectomy group (p = 0.376, p = 0.128). Conclusion Postoperative Eustachian tube dysfunction is seen less often with the endoscopic-assisted microdebrider adenoidectomy technique than with the conventional adenoidectomy technique.